The Interrelationship Between Water Use Efficiency and Radiation Use Efficiency Under Progressive Soil Drying in Maize - Zhou, Huailin; Zhou, Guangsheng; Zhou, Li; Lv, Xiaomin; Ji, Yuhe; Zhou, Mengzi (Frontiers in Plant Science, 2021)
Maximizing water and radiation use efficiencies (WUE and RUE, respectively) are vital to improve crop production in dryland farming systems. However, the fundamental question as to the association of WUE with RUE and its underlying mechanism under limited-water availability remain contentious. Here, a two-year field trial for maize designed with five progressive soil drying regimes applied at two different growth stages (three-leaf stage and seven-leaf stage) was conducted during 2013-2014 growing seasons. Environmental variables and maize growth traits at the leaf and canopy levels were measured during soil drying process. The results showed that leaf WUE increased with irrigation reduction at early stage, while decreased with irrigation reduction at later stage. Leaf RUE thoroughly decreased with irrigation reduction during progressive soil drying process. Aboveground biomass (AGB), leaf area index (LAI), fraction of absorbed photosynthetically active radiation (fAPAR) and light extinction coefficient (k) of the maize canopy were significantly decreased by water deficits regardless of the growth stages when soil drying applied. The interrelationships between WUE and RUE were linear across the leaf and canopy scales under different soil drying patterns. Specifically, a positive linear relationship between WUE and RUE were unexpectedly found when soil drying applied at three-leaf stage, while it turned out to be negative when soil drying applied at seven-leaf stage. Moreover, the interaction between canopy WUE and RUE was more regulated by fAPAR than LAI under soil drying. Our findings suggest to pay more attention to fAPAR in evaluating the effect of drought on crops and may bring new insights into the interrelationships of water and radiation use processes in dryland agricultural ecosystems.